The effect of waste foundry sand as partial sand replacement towards porosity and chloride resistance in mortar - Nurulfaizah , Mohd Ismail (2012)
Waste foundry sand (WFS) is high quality silica sand that is a byproduct from the production of both ferrous and nonferrous metal casting. In metal casting process, molding sand which is foundry sand is recycled and re-used for several times until it no longer can be used. The large amount of waste foundry sand demand more landfill space. The research should be continuously done to investigate about the potential of waste foundry sand to be reused in various types of field such as construction, highway and geotechnical applications. For this research, the properties of mortar containing different percentage of waste foundry sand (0%,10%,20% and 30%) as partial replacement of naturals sand were investigated towards porosity and chloride resistance. The type of waste foundry sand used was silica sand with sodium silicate as a binder. Vacuum saturation test was done to determine the porosity and two tests for chloride resistance which were open circuit potential (OCP) test and impressed voltage test. From the result, it was found that the waste foundry sand has a potential to be used in mortar to reduce the porosity and increase the resistance towards chloride attack. The waste foundry sand can be used as a partial sand replacement in mortar and the optimum percentage of partial sand replacement was up to 10% of waste foundry sand in mortar.